TRICKSTER SAINTS AND THEIR MANIFESTATIONS AND MIRACLES IN LATE ANTIQUE HAGIOGRAPHY - Doroszewska, Julia, 1981- Link ([S.l.])
1 online resource
Keywords: This book explores how late antique miracle collections depict Christian saints as subversive, theatrical tricksters who blur the boundaries between sacred and profane, human and divine.Readers will gain a fresh perspective on the cultural and theological imagination of Late Antiquity through a detailed analysis of Greek hagiographic texts. Doroszewska combines literary, religious, and anthropological approaches to show how saints functioned as shape-shifting, paradoxical figures - divine jesters who used ambiguity, humour, and disruption to communicate the sacred. The chronological framework of this study spans from the fifth to the seventh/ eighth century, exploring the emergence, heyday, and eventual decline of miracle collections following the Arab conquest. The volume demonstrates that idiosyncrasies in the characterization of the saints in these texts form a coherent model when approached with the template of the trickster paradigm, offering readers a new understanding of sainthood in late antique Christianity.Trickster Saints and Their Manifestations and Miracles in Late Antique Hagiography is suitable for scholars and students of late antique Christianity, hagiography, religious studies, classical studies, and those interested in the intersections of literature, folklore, and cultural history.